Impact of local iron enrichment on the small benthic biota in the deep Arctic Ocean - Soltwedel, Thomas; Rapp, Josephine Z.; Hasemann, Christiane (Frontiers in Marine Science, 2023)
This study assesses the impact of local iron enrichment on the small benthic biota (bacteria, meiofauna) at the deep seafloor. To evaluate the hypothesis that abundance, distribution, and diversity of the small benthic biota varies in relation to a local input of structural steel at the seabed, we analyzed sediment samples and the associated infauna along a short transect ( 1.5 m in length) with increasing distance to an iron source, i.e., corroding steel weights (30 cm in length and width, and 6 cm in height) of a free-falling observational platform (bottom-lander), lying on the seafloor for approximately seven years. Bacterial and meiofaunal densities and biomasses in iron-enriched sediments were significantly lower than those in unaffected sediments. Moreover, bacterial and nematode community structure between iron-enriched sediments and unaffected sediments differed strongly; taxonomic richness as well as diversity was lowest closest to the iron source. The presence of iron fostered the establishment of specialized iron oxidizers and other chemolithoautotrophic bacterial members, which were rare or absent in the unaffected sediments, within which opportunistic heterotrophs predominated. Nematodes comprised >90% of the total metazoan meiofauna and were therefore studied in more detail. A total of 26 genera from 16 families occurred in iron-enriched sediments (three genera were found exclusively in these sediments), while 65 genera from 27 families occurred in the unaffected sediments (39 genera and 12 families were found exclusively in these sediments). Nematode genera number (S), estimated genera richness (EG(51)) and heterogeneity (H’(log2)) were significantly lower in iron-enriched sediments than in unaffected sediments. Our results confirm that the local enrichment of deep-sea sediments by metallic and corroding structures (e.g., by ship hulls, containers, scientific equipment) strongly affects the diversity of the small benthic biota at short distances from these sources.